Bifidobacterium longum CECT 7894 Improves the Efficacy of Infliximab for DSS-Induced Colitis via Regulating the Gut Microbiota and Bile Acid Metabolism - Xiao, Fangfei; Dong, Fang; Li, Xiaolu; Li, Youran; Yu, Guangjun; Liu, Zhanju; Wang, Yizhong; Zhang, Ting (Frontiers in Pharmacology, 2022)
Background: Recent evidences suggested that the changes in gut microbiota and its metabolites could predict the clinical response of anti-tumor necrosis factor agents, such as infliximab (IFX). However, whether manipulation of the gut microbiota can enhance the efficacy of anti-TNF agents remains unclear. Here, we aimed to evaluate the effect of a probiotic strain, Bifidobacterium longum (B. longum) CECT 7894 on IFX efficacy for dextran sulfate sodium (DSS)-induced colitis in mice, and attempt to explore the potential involved mechanisms. Methods: C57BL/6 mice were treated with PBS or B. longum CECT 7894 (5× 108 CFU/day) once daily by gavage for 5 days and subsequently induced acute colitis by 3% (w/v) DSS in drinking water. The efficacies of IFX combined with or without B. longum CECT 7894 were assessed by weight loss, fecal consistency, colon length and histopathological changes. Immunohistochemistry (IHC) was used to examine the tight junction proteins expressions in colonic tissues. The microbiota composition was characterized through 16S rRNA gene sequencing. Fecal bile acids (BAs) levels were analyzed by targeted metabolomics. Results: B. longum CECT 7894 improved the efficacy of IFX for DSS-induced colitis as evidenced by decreased weight loss, disease activity index (DAI) scores, colon length shortening, histological damage, and increased ZO-1, Occludin expressions as compared with mice received IFX only. B. longum CECT 7894 modified the composition and structure of the gut microbiota community in DSS-induced colitis mice. B. longum CECT 7894 increased the relative abundances of genera Bifidobacterium, Blautia, Butyricicoccus, Clostridium, Coprococcus, Gemmiger, and Parabacterioides, and reduced the relative abundances of bacteria genera Enterococcus and Pseudomonas. Furthermore, B. longum CECT 7894 changed the BAs metabolism by increasing the abundances of secondary BAs, such as α-MCA, β-MCA, LCA, CDCA, UDCA, HCA, isoLCA, isoalloLCA. The covariance analysis revealed the upregulated secondary BAs were positively associated with the increased abundances of bacteria that contain bile salt hydrolases and 7α-dehydroxylases genes. Conclusion: B. longum CECT 7894 improved the efficacy of IFX for DSS-induced colitis via regulating the gut microbiota composition and bile acid metabolism. Probiotics supplementation may provide a possibility to improve the clinical response of anti-TNF agents in IBD management.